Superficial Medial Collateral Ligament Anatomic Augmented Repair Versus Anatomic Reconstruction: An In Vitro Biomechanical Analysis. (December 2013) - Wijdicks, Coen A.; Michalski, Max P.; Rasmussen, Matthew T.; Goldsmith, Mary T.; Kennedy, Nicholas I.; Lind, Martin; Engebretsen, Lars; LaPrade, Robert F.
Background: When surgical intervention is required for a grade 3 superficial medial collateral ligament (sMCL) tear, there is no consensus on the optimal surgical treatment. Anatomic augmented repairs and anatomic reconstructions for treatment of grade 3 sMCL tears have not been biomechanically validated or compared. Hypothesis: Anatomic sMCL augmented repairs and anatomic sMCL reconstruction techniques will reproduce equivalent knee kinematics when compared with the intact state, while creating significant improvements in translational and rotational laxity compared with the sMCL sectioned state. Study Design: Controlled laboratory study. Methods: Eighteen match-paired, fresh-frozen cadaveric knees (average age, 52.6 years; range, 40-59 years) were each used to test laxity of an intact sMCL, a deficient sMCL, and either an anatomic augmented repair or an anatomic reconstruction. Knees were biomechanically tested in a 6 degrees of freedom robotic system, which included valgus rotation, internal and external rotation, simulated pivot shift, and coupled anterior drawer with external rotation. Results: Anatomic augmented repairs and anatomic reconstructions had significantly less medial joint gapping than the sectioned state at all tested flexion angles and showed significant reductions in valgus rotation compared with the sectioned state at all flexion angles. No significant differences between the anatomic augmented repair and anatomic reconstruction were found for any test performed. Despite the similar behavior between the 2 reconstruction groups, neither technique was able to reproduce the intact state. Conclusion: Anatomic sMCL augmented repairs and anatomic sMCL reconstructions were not significantly different when tested at time zero. Both the anatomic augmented repair and the anatomic reconstruction were able to improve knee stability and provide less than 2 mm of medial joint gapping at 0° and 20° of flexion. Clinical Significance: These results suggest that both an anatomic sMCL augmented repair and an anatomic sMCL reconstruction improve knee kinematics compared with a deficient sMCL and provide equivalent joint stability.